Method for inducing and constructing topological domain by introducing oxygen vacancies from bottom electrode

By depositing the bottom electrode on a single crystal substrate and introducing oxygen vacancies defects, combined with the method of deposition of bismuth ferrate film by pulsed laser, a uniform and unified topological domain is constructed, solving the problems of complex processes and low storage density in the prior art, and achieving high-density ferroelectric memory devices.

CN119730696APending Publication Date: 2025-03-28HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411760949.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to construct topological domains evenly and uniformly under the conditions of simple process and large preparation amount, which limits its application in ferroelectric memory devices.

Method used

By depositing the bottom electrode on a single crystal substrate, covering the conical AAO template, introducing oxygen vacancy defects using Ar+ ion beam etching, and after removing the template, a pulsed laser deposits a bismuth ferrate film to construct topological domains.

Benefits of technology

The spontaneously polarized topological domain construction is realized, the process is simple and can be prepared in large batches. The obtained polarized topological domain array has a high density, which solves the problem of low storage density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730696A_ABST
    Figure CN119730696A_ABST
Patent Text Reader

Abstract

The invention discloses a method for inducing and constructing a topological domain by introducing oxygen vacancies from a bottom electrode. The method comprises the following steps of: depositing the bottom electrode on a single-crystal substrate by utilizing a pulse laser deposition technology; covering the bottom electrode with a conical AAO template; an Ar < + > ion beam penetrates through the conical AAO template to etch the bottom electrode, and an oxygen vacancy defect is introduced; the conical AAO template is removed, a bismuth ferrite film is deposited on the bottom electrode through pulse laser, and topological domain construction is completed; checking the uniformity of the topological domain structure through characterization; according to the invention, the ferroelectric layer can be induced to spontaneously form head-to-head or tail-to-tail polarization distribution, so that a central or vortex topological structure and an array thereof can be constructed; the preparation method is simple in process and can be used for large-scale and industrial preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for constructing a topological domain, in particular to a method for introducing oxygen vacancies from a bottom electrode to induce the construction of a topological domain, and belongs to the technical field of micro-nano structures. Background Art

[0002] Polarization topological defects have attracted widespread attention because they can greatly improve the storage density of ferroelectric memory. In addition to the common vortices and anti-vortices, there are also bubble domains, skyrmions, radial central domains, etc., which are all polar topological defects. Researchers have detected vortices and their periodic arrays in grown PbTiO3 / SrTiO3 multilayer films and superlattices. For samples containing volatile and toxic lead, irreversible harm will be caused to the environment and human body; they are all produced in confined or confined structures, requiring the growth of more than 10 layers, and high requirements for the preparation process; the bottomless electrode does not affect the controllable flipping of the domain, resulting in its inability to be integrated into the device. Other researchers have used external fields, especially the electric field generated by the tip bias, to construct polarization bubble domains in ferroelectric ceramics, and vortices and central topological domains in thin films. However, the market still needs a preparation method that can produce spontaneous polarization.

[0003] Compared with the above methods, the vortex domain has been detected by etching the film with AAO as the template to obtain the nanodot array. This method is simple to operate and has mature technology, but the topological domains obtained are not uniform enough, and its application prospects are limited. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for introducing oxygen vacancies from the bottom electrode to induce the construction of topological domains, which can simplify the process and increase the preparation amount.

[0005] Technical solution: The method of introducing oxygen vacancies from the bottom electrode to induce the construction of topological domains described in the present invention comprises:

[0006] S1: Depositing the bottom electrode on a single crystal substrate using pulsed laser deposition technology;

[0007] S2: Cover the bottom electrode with a conical AAO template;

[0008] S3: Using Ar + The ion beam passes through the tapered AAO template to etch the bottom electrode, introducing oxygen vacancy defects;

[0009] S4: Remove the conical AAO template and pulse laser deposit bismuth ferrite film on the bottom electrode to complete the topological domain construction.

[0010] Furthermore, the step S1 specifically includes pulse laser deposition of a bottom electrode SrRuO3 on a single crystal substrate SrTiO3, and the thickness of the SrRuO3 layer is 20-25 nm.

[0011] Furthermore, in the preparation parameters of the pulsed laser deposition of the bottom electrode SrRuO3 on the single crystal substrate SrTiO3, the pulsed laser energy is 300mJ, the pulse frequency is 8Hz, the temperature is 700°C, the oxygen pressure is 10Pa, and the thickness of the SrRuO3 layer is 20-25nm.

[0012] Furthermore, the conical AAO template described in step S2 is a nanoporous template prepared by anodizing aluminum.

[0013] Furthermore, the conical AAO template in step S2 has an opening pore diameter of 90 to 200 nm, a lower end pore diameter of 10 to 40 nm, a pore spacing of 60 to 100 nm, and a pore depth of 200 to 300 nm.

[0014] Furthermore, the step S3 is specifically, the Ar + The ion beam is at room temperature and the vacuum degree is 8.0×10 - 4 Pa, maintain the cathode current of the ion beam etching system at 15.0A, the anode voltage at 50V, the screen voltage at 300V, the acceleration voltage at 250V, the neutralization current at 13A, and the bias voltage at 1.0V, and perform etching for 20 to 30s.

[0015] Furthermore, the method for removing the conical AAO template in step S4 is to tear off the conical AAO template by using a tape stripping method.

[0016] Furthermore, in the preparation parameters of the pulsed laser deposition of bismuth ferrite film in step S4, the pulsed laser energy is 1 mJ / cm 3 , the pulse frequency is 12 Hz, the temperature is 680°C, the oxygen pressure is 5 Pa, and the thickness of the bismuth ferrite film is 20 to 30 nm.

[0017] Furthermore, the method further comprises: step S5, testing the uniformity of the topological domain structure by characterization.

[0018] Furthermore, the characterization inspection method described in step S5 is a vector PFM method, which completes the verification by providing the sample's morphology and PFM image, as well as out-of-plane PFM / VPFM images and in-plane PFM / LPFM images, and reconstructing the three-dimensional polarization vector distribution of the topological domain in space.

[0019] Beneficial effects: Compared with the prior art, the present invention introduces oxygen vacancies by ion beam etching the bottom electrode, which can induce the ferroelectric layer to spontaneously form a head-to-head or tail-to-tail polarization distribution, thereby constructing a central or vortex topological structure and its array; the preparation method is not only simple in process, but also can be prepared in large quantities and industrially; the polarization topological domain array finally obtained has a high density, which is expected to effectively solve the technical bottleneck of low storage density faced by ferroelectric random access memory devices on the current market. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a flow chart of a method according to an embodiment of the present invention;

[0021] Figure 2 This is a schematic diagram of a pulsed laser deposited bottom electrode according to an embodiment of the present invention;

[0022] Figure 3 Schematic diagram of pulsed laser deposition of bismuth ferrite film according to an embodiment of the present invention;

[0023] Figure 4 This is a morphology diagram of a conical AAO template according to an embodiment of the present invention;

[0024] Figure 5 is a morphology diagram of a SrRuO3 film according to an embodiment of the present invention;

[0025] Figure 6 The EPR spectra of the SrRuO3 film before and after etching according to the embodiment of the present invention;

[0026] Figure 7 is an X-ray diffraction pattern of a BiFeO3 thin film according to an embodiment of the present invention;

[0027] Figure 8 The PFM piezoelectric loop diagram of the BiFeO3 film according to an embodiment of the present invention;

[0028] Fig. 9 Schematic diagram of a topological domain array obtained by PFM characterization according to an embodiment of the present invention. DETAILED DESCRIPTION

[0029] In order to make those skilled in the art better understand the present application scheme, the technical scheme in the present application embodiment will be clearly and completely described below in conjunction with the accompanying drawings in the present application embodiment. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the present application.

[0030] As attached Figure 1As shown, the method of introducing oxygen vacancies from the bottom electrode to induce construction of topological domains in this embodiment includes:

[0031] Step S1, using pulsed laser deposition (PLD) technology to deposit the bottom electrode. Prepare a SrTiO3 (STO) single crystal substrate, such as Figure 2 As shown in (a), a SrRuO3 (SRO) bottom electrode film is deposited thereon. Figure 2 (b) As shown in the figure, the pulsed laser deposition method uses a stoichiometric SrRuO3 ceramic target and produces a 25nm thick SrRuO3 film by strictly controlling parameters such as oxygen pressure, temperature, laser energy density, and pulse frequency.

[0032] Step S2, covering the bottom electrode with a conical AAO (Anodic Aluminum Oxide) template, such as Figure 2 (c) As shown. The conical AAO template is a pore structure that transforms the vertical pores of the AAO template into a pore structure with a large pore size at the upper end and a small pore size at the lower end. The opening pore size is 90nm, the lower pore size is 40nm, the pore spacing is 100nm, and the pore depth is 200nm. The morphology of the upper surface of the AAO template was characterized by atomic force microscopy, as shown in Figure 4 As shown, the porous structure of the AAO template can be clearly seen, and its pore size and pore spacing can be easily obtained.

[0033] Step S3, using Ar + The ion beam passes through the template etching (IBE) bottom electrode to introduce oxygen vacancy defects. The model of the ion beam etcher is MIBE-150C. Under room temperature conditions, the vacuum degree is 8.0×10 -4 Pa, maintain the cathode current of the ion beam etching system at 15.0A, the anode voltage at 50V, the screen voltage at 300V, the acceleration voltage at 250V, the neutralization current at 13A, and the bias voltage at 1.0V, and perform etching for 20 to 30s. Atomic force microscopy was used to characterize the morphology of the bottom electrode film, such as Figure 5 As shown, the roughness (rms) of the film is 500 pm, indicating that the film surface is flat; by adjusting the image contrast, it can be seen that some areas (dark contrast areas) have depressions, but the height difference is not obvious, indicating that the shorter etching time does not significantly change the film surface morphology, such as etching out pits. EPR measurement is a direct and effective method to determine the presence of oxygen vacancies in materials, such as Figure 6 As shown, the etched bottom electrode film has a representative EPR signal at g = 2.002, revealing electron capture on oxygen vacancies.

[0034] Step S4, removing the conical AAO template, and depositing a bismuth ferrite (BiFeO3, BFO) film by pulsed laser, such as Figure 3As shown. The conical AAO template is removed by mechanical stripping, using tape to stick and then tear off the porous conical AAO template. The preparation parameters of pulsed laser deposition of bismuth ferrite film are: energy of 1mJ / cm 3 , pulse frequency 12Hz, temperature 680℃, oxygen pressure 5Pa. The thickness of the deposited bismuth ferrite film is 20-30nm. X-ray diffraction θ-2θ scanning characterization, such as Figure 7 As shown in the figure, the results clearly show the epitaxial structure of STO / SRO / BFO. The lattice constant calculated from the out-of-plane (001) peak shows that the BFO film is a rhombohedral phase structure. In order to prove the ferroelectricity of the sample, the PFM piezoelectric loop of the sample is characterized using the "piezoelectric-hysteresis" mode. Figure 8 The upper part shows that the PFM phase diagram has changed by 180°. Figure 8 The lower part is the normalized PFM amplitude diagram, which is a butterfly-shaped piezoelectric loop. The PFM piezoelectric loop shows that the coercive field of the BFO film is ±3.8V and very symmetrical, indicating that the sample has good ferroelectric properties.

[0035] Step S5, the uniformity of the topological domain structure is verified by characterization. Vector PFM gives the morphology of the sample, such as Fig. 9 As shown in (a), it can be seen that the surface of the film has large fluctuations, indicating that the surface flatness of the film has decreased. Fig. 9 (b) shows the schematic diagram of two polarized skyrmion domains. Vector PFM also gives the VPFM image (e.g. Fig. 9 (c) and Fig. 9 (d)) and LPFM images (as shown Fig. 9 (e) and Fig. 9 (f)), the three-dimensional polarization vector distribution of the topological domain in space can be reconstructed. By combining the data of a VPFM image and two LPFM images, the three-dimensional polarization vector distribution of the topological domain in space can be reconstructed. Fig. 9 (c) and Fig. 9 (e) shows that the out-of-plane polarization of the film has a bubble-like domain structure, while the in-plane polarization is a smaller domain structure. Fig. 9 (d) and Fig. 9 From the internal bright contrast and external dark contrast of (f), it can be seen that the out-of-plane polarization of the film is more of an internal downward and external upward contrast distribution, and the in-plane polarization includes head-to-head and tail-to-tail distribution. Through polarization reconstruction, two types of polarized skyrmion domains with center upward and center downward are finally obtained. These uniform topological domains can be used in high-density ferroelectric memory devices.

Claims

1. A method for inducing topological domain construction by introducing oxygen vacancies from a bottom electrode, characterized in that: include: S1: Depositing the bottom electrode on a single crystal substrate using pulsed laser deposition technology; S2: Cover the bottom electrode with a conical AAO template; S3: Using Ar + The ion beam passes through the tapered AAO template to etch the bottom electrode, introducing oxygen vacancy defects; S4: Remove the conical AAO template and pulse laser deposit bismuth ferrite BFO film on the bottom electrode to complete the topological domain construction.

2. The method for inducing topological domain construction by introducing oxygen vacancies from the bottom electrode according to claim 1, characterized in that: Specifically, the step S1 is to deposit a bottom electrode SrRuO3 on the single crystal substrate SrTiO3 by pulse laser, and the thickness of the SrRuO3 layer is 20-25 nm.

3. The method for inducing construction of topological domains by introducing oxygen vacancies from a bottom electrode according to claim 2, characterized in that: The preparation parameters of the pulsed laser deposition bottom electrode SrRuO3 on the single crystal substrate SrTiO3 are as follows: the pulsed laser energy is 300mJ, the pulse frequency is 8Hz, the temperature is 700°C, the oxygen pressure is 10Pa, and the thickness of the SrRuO3 layer is 20-25nm.

4. The method for inducing topological domain construction by introducing oxygen vacancies from a bottom electrode according to claim 1, characterized in that: The conical AAO template described in step S2 is a nanoporous template prepared by anodizing aluminum.

5. The method of introducing oxygen vacancies from a bottom electrode to induce construction of topological domains according to claim 1, characterized in that: The conical AAO template described in step S2 has an opening pore diameter of 90 to 200 nm, a lower end pore diameter of 10 to 40 nm, a pore spacing of 60 to 100 nm, and a pore depth of 200 to 300 nm.

6. The method of introducing oxygen vacancies from a bottom electrode to induce construction of topological domains according to claim 1, characterized in that: The step S3 specifically comprises: + The ion beam is at room temperature and the vacuum degree is 8.0×10 -4 Pa, maintain the cathode current of the ion beam etching system at 15.0A, the anode voltage at 50V, the screen voltage at 300V, the acceleration voltage at 250V, the neutralization current at 13A, and the bias voltage at 1.0V, and perform etching for 20 to 30s.

7. The method of introducing oxygen vacancies from a bottom electrode to induce construction of topological domains according to claim 1, characterized in that: The method for removing the conical AAO template in step S4 is to tear off the conical AAO template by using a tape stripping method.

8. The method of introducing oxygen vacancies from a bottom electrode to induce construction of topological domains according to claim 1, characterized in that: In the preparation parameters of the pulsed laser deposition of bismuth ferrite film in step S4, the pulsed laser energy is 1 mJ / cm 3 , the pulse frequency is 12 Hz, the temperature is 680°C, the oxygen pressure is 5 Pa, and the thickness of the bismuth ferrite film is 20 to 30 nm.

9. The method of introducing oxygen vacancies from a bottom electrode to induce construction of topological domains according to claim 1, characterized in that: The method further comprises: step S5, testing the uniformity of the topological domain structure by characterization.

10. The method for inducing construction of topological domains by introducing oxygen vacancies from a bottom electrode according to claim 9, characterized in that: The characterization inspection method described in step S5 is the vector PFM method, which completes the verification by providing the sample's morphology and PFM image, as well as the out-of-plane PFM / VPFM image and the in-plane PFM / LPFM image, and reconstructing the three-dimensional polarization vector distribution of the topological domain in space.